Participants' physical activity levels and evaluations of a school sport programme in Papua New Guinea. (February 2019) - Hanrahan, Stephanie; Rynne, Steven; Beckman, Emma; Rossi, Tony
In its contemporary form, sport for development has been positioned as an important part of strategic policy for a variety of governmental and sporting organisations. One area that has been targeted by governments and a variety of sporting partners has been the impact of sport on non-communicable diseases (NCDs, sometimes colloquially referred to as 'lifestyle diseases' such as obesity). However, relatively little evidence exists for the impact of sport programmes on the reduction of NCDs and future health burden. This study sought to examine the physical activity levels of school-aged children in Papua New Guinea (PNG) during their participation in a targeted sport programme operating during school hours. Data collection methods employed were physical activity recall and pedometer counts, as well as perceptions, intentions, and knowledge of participants. Children in this study were found to have lower physical activity levels during the after-school period than has been reported in the literature for children in other countries. Overall, children were active during the sport programme, completing 1179 steps on average (which constitutes 10% of the suggested daily values for children of a similar age). No profound differences were observed in either the qualitative or quantitative data across different schools, regions, or genders. The responses from children regarding the sport programme were notably positive.